“Obtención de productos crocantes tipo “SNACKS” por fritura de maiz amarillo ( Zea Mays) y dos variedades de frijol ( phaseolus vulgaris); Huasca alipa - Espiritu Cisterna, Christoper Markus (2001)
The consumption of leguminous of grain and cerea Is constitute an important protein source especially in the countries in development, he/she has gone year after year in constant decrease. As a way of reve1ting this situation, it is looked for to design processes that allow to obtain a product, of easy use and with smaller time of elaboration. In such a sense to increase the consumption of leguminous and cereals in our feeding you development a product type " snack" based on fried frijol using for it two varieties: huasca and allpa (Phaseolus vulgaris L), which underwent two soaking solutions: to) salt disódica EDTA and b) NaOH/H20 mixes; determining if these soaking types had sorne effect on the finai quality of the products. On the other hand, before the beans underwent the fritter process half of the grains they were treated thermally (parboiled) to 95ºC x 5 min. and the other half without thermal treatment (raw). you Also determines the influence of the soaking on the final quality of the corn and the fried beans. To the obtained fried products they were determined their. physical, chemical and sensorial characteristics. In the two frijol varieties, the parboiled products presented bigger content of humidity, a smaller absorption of oíl, bigger quantity of fiber, smaller caloric contribution, not being effect of the soaking solutions on the quality of the elaborated products. On the other hand the sensorial analysis determined that the best thermal treatment for each variety of studied frijol was: 1 soak in EDTA and treatment in raw for the beans frijol huasca and allpa. To improve the quality of the protein contributed by the products type "snack" frijol mixtures they were formulated - corn fried in different proportions: 60: 40 (A); 50: 50 (B) and 40: 60 (C). The fried corn used to carry out these samples underwent a single soaking solution NaOH/EDT A and later on the half was subjected to thermal treatment (parboiled) to 95ºC x 5 min. and the other half without thermal treatment (raw). The sensorial analysis determined that the best treatment for the fried corn was the NaOH/EDTA in having parboiled, being better in Acceptability, appearance, texture and crocancia. The selected treatments of each frijol cultivation (hausca and allpa) and the hard yellow corn already mixed in the proportions described, being formulated 6 mixtures those that were characterized chemical and sensorily, constituting a third objective of the study to obtain the best mixture vegetable -cereal. These mixtures turned out to be very homogeneous in all their analyzed characteristics. One could observe that the protein content of the mixture A ( 18. 90 and 17.40 for huasca and allpa respectively), it was the but high of the other two proportions, but in the sensorial analysis 1 am the second but accepted. The election of the best mixture vegetable - cereal one carries out for the sensorial analysis of acceptability, in which was the proportion C the best, turning out also apparently to be better and color.